Indigofera pulchra leaves extracts contain anti-Plasmodium berghei agents (Bangladesh Journal of Pharmacology, 2011)
This study was conducted to investigate the anti-Plasmodium berghei activities of some extracts from Indigofera pulchra leaves. Six groups of mice were intraperitoneally infected with chloroquine sensitive P. berghei (NK 65) among which two groups were orally treated with 100 and 200 mg/kg body weight of methanol leaves extract while another two groups were treated with 100 and 200 mg/kg of n-butanol fraction derived from the methanol extract. Another infected group was treated with chloroquine (25 mg/kg) whereas the remaining infected group was left untreated. All infected treated groups possessed a significantly (p